The Effect of Product Quality and Product Packaging on Purchasing Decisions of Caca Cassava Chips in Lahat City - Rini Asti Anggraini; Darwin Kesuma; Mujari Mujari (Universitas Dehasen Bengkulu, 2026)
The objectives of this research include: to determine the effect of product quality on purchasing decisions of Caca cassava chips in Lahat City, to determine the effect of product packaging on purchasing decisions of Caca cassava chips in Lahat City and to determine the effect of product quality and product packaging together on purchasing decisions of Caca cassava chips in Lahat City. The sample of this research is consumers of Caca cassava chips in Lahat City, totaling 250 people. This research uses quantitative research, using data sources including: primary data, secondary data, population and samples. Data collection methods used are: observation, interviews and distribution of questionnaires to a number of respondents. As well as using validity and reliability measuring tools, analysis prerequisite tests, then using data analysis methods using multiple regression analysis, hypothesis testing in the form of t-tests and F-tests. As well as correlation coefficients and determination coefficients. Data analysis in this study uses SPSS 23.0. From the research results, a partial t-test showed that the product quality variable had a calculated t-value > t-table value, or 3.812 > 2.661. Therefore, Ho was rejected and Ha was accepted. This indicates a significant influence between the product quality variable and the purchasing decision variable. The product packaging variable had a calculated t-value > t-table value, or 4.049 > 2.661. Therefore, Ho was rejected and Ha was accepted. This indicates a significant influence between the product packaging variable and the purchasing decision variable. The F-test results, with a significance level of 5% and a numerator df of 3 and a denominator df of 250, were 2.64. Based on the results of this hypothesis test, the decision was made to reject Ho and accept Ha. This means that the product quality and packaging variables collectively have a significant influence on the purchasing decision variable.